Periodontal healing following reconstructive surgery: effect of guided tissue regeneration using a bioresorbable barrier device when combined with autogenous bone grafting. A randomized controlled clinical trial - Per Nygaard-ÃƒÆ’Ã‹Å“stby, Vibeke Bakke, (2008)
Objective: The objective of this randomized-controlled clinical trial was to evaluate the adjunctive effect of guided tissue regeneration (GTR) using a bioresorbable polylactic acid (PLA) barrier device when combined with autogenous bone grafting in the treatment of deep intra-bony periodontal defects. Material and Methods: Forty systemically healthy patients (20 females; mean age 53 years; non-smokers) participated in the study. Using a parallel-group study design, one intra-bony defect in each of 20 subjects received GTR using the bioresorbable PLA barrier device (Atrisorbs), combined with autogenous bone grafting. One intra-bony defect in each of the remaining 20 subjects received bone grafting solo (control). Treatments were evaluated at 9 months post-surgery. Results: One patient (GTR) was withdrawn from the study due to circumstances unrelated to the study. Eighty-nine per cent of the PLA barriers became exposed within 3 weeks following surgery. Pre-surgery probing depths for GTR and control intra-bony defects averaged ( SE) 7.1 0.3 mm. Significant probing depth reduction (2.7 0.3 versus 2.4 0.4 mm), attachment-level gain (1.7 0.3 versus 1.7 0.5 mm), and bone fill (1.2 0.4 versus 1.2 0.5 mm) were observed for the GTR and control sites, respectively (p40.02). However, there were no statistically significant differences between treatment protocols. Conclusions: The results suggest that GTR using the bioresorbable PLA barrier device does not provide additional value to reconstructive surgery including autogenous bone grafting in intra-bony periodontal defects.